The Public Library and Social Capital: Examining the Role of Public Libraries in Building Social Cohesion - Johnson, Catherine; Griffis, Matthew (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper examines the role of the public library in building strong communities. It reports on a study that asked patrons through interviews and questionnaires about their use of the library and explores whether this use has had an effect on the creation of both community and individual social capital. Cet article examine le rôle de la bibliothèque publique dans le renforcement des collectivités. Seront présentés les résultats d'entrevues auprès d'usagers et d'un questionnaire portant sur l'utilisation de la bibliothèque ainsi qu'une exploration de l'effet de cette utilisation sur la création d'un capital social collectif et individuel.